A closer look at Carver and White's BIS/BAS scales: Factor analysis and age group differences. (June 2016) - Gray, Joshua D.; Hanna, Donncha; Gillen, Allison; Rushe, Teresa
Abstract: The Behavioural Inhibition and Behavioural Activation System (BIS/BAS) scales were developed by Carver and White (1994) and comprise four scales which measure individual differences in personality (Gray 1982, 1991). More recent modifications, namely the five-factor model derived from Gray and McNaughton's (2000) revised Reward Sensitivity Theory (RST) suggests that Anxiety and Fear are separable components of inhibition. This study employed exploratory and confirmatory factor analyses on the scales in order to test whether the four or five-factor model was the better fit in a sample of 994 participants aged 11–30 years. Consistent with RST, superior model fit was shown for the five-factor model with all variables correlated. Significant age effects were observed for BIS Fear and BIS Anxiety, with scores peaking in middle and late adolescence respectively. The BAS subscales showed differential effects of age group. Significantly increasing scores from early to mid and from mid to late adolescence were found for Drive, but the effect of age on Fun Seeking and Reward Responsiveness was not significant. Highlights: Factor analyses of the BIS/BAS scales suggest Anxiety and Fear are separable components of inhibition. Anxiety, Fear and Drive scores are the highest in adolescence. Females have higher Anxiety than males. Reward Responsiveness and Fun Seeking score are not affected by age group.